2020
DOI: 10.1186/s12885-020-6517-0
|View full text |Cite
|
Sign up to set email alerts
|

Young-onset gastric cancer and Epstein–Barr Virus (EBV) – a major player in the pathogenesis?

Abstract: Objective: Gastric cancer (GC) is a leading cause of cancer death, occurs predominantly in older age, with increasing incidence in young patients. The Cancer Genome Atlas indicates four subtypes for GC among which Epstein-Barr virus (EBV) subtype is estimated at 8.7%. We aim to determine the prevalence of EBV subtype in young GC patients (≤45 years) compared with an average-onset cohort (≥55 years) and characterize the clinicopathologic pattern of young-onset GC. Methods: Gastric cancer samples of patients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
4
17
0
1
Order By: Relevance
“…Our findings are also corroborated by the study by Moore et al [41], who found that the subtype of GC EBV-positive is indicative of a good prognosis and is more prevalent in young patients, as in the present study, where the number of young patients is statistically higher than patients older than 64 years of age (p < 0.0001). Another study with a large number of samples (n = 3241) also found results similar to our findings, EBV-positive patients (5%) were young and male, with GC samples histologically poorly differentiated, and patients having a good prognosis when expressing the PD-L1 protein [38].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also corroborated by the study by Moore et al [41], who found that the subtype of GC EBV-positive is indicative of a good prognosis and is more prevalent in young patients, as in the present study, where the number of young patients is statistically higher than patients older than 64 years of age (p < 0.0001). Another study with a large number of samples (n = 3241) also found results similar to our findings, EBV-positive patients (5%) were young and male, with GC samples histologically poorly differentiated, and patients having a good prognosis when expressing the PD-L1 protein [38].…”
Section: Discussionsupporting
confidence: 93%
“…The evidence in the literature regarding the role of sex in young-onset gastrointestinal adenocarcinoma has been mixed, with some studies reporting a greater incidence rate in males for oesophageal, stomach, and colon and rectal cancers [ 32 , 33 , 34 ], while others reporting females showing greater incidence rates for colon cancer [ 35 ]. This study has demonstrated that the incidence of young-onset gastrointestinal adenocarcinomas has significantly increased in males and females between the ages of 18 and 50 years, with the increase being more pronounced in males.…”
Section: Discussionmentioning
confidence: 99%
“…The cases in the present study were derived from more than 1,328 samples, which is the largest number of cases reported thus far for the overall analysis of the immune microenvironment. A study involving Americans reported the greater prevalence of the EBV subtype in young-onset GC, which might play a key role in the pathogenesis ( 17 ). A Japanese study found that an age <65 years was an independent risk factor for lymph node metastasis in patients with EBVaGC ( 18 ).…”
Section: Discussionmentioning
confidence: 99%